Exploring 11th-grade students’ mathematical reasoning ability on sequences and series: A qualitative study - Faridah, Nurul; Marlina, Ratna (CV. Pustaka Literasi Ilmiah, 2025)
This study aims to provide an analytical description of how students solve five essay questions aligned with indicators of mathematical reasoning ability. A descriptive qualitative method was employed, with a purposive sample of seven 11th-grade high school students in West Bandung Regency. Data were collected through students’ written responses to test instruments and subsequently analyzed to identify errors in the problem-solving process and to measure mathematical reasoning skills. The measured indicators included: (1) formulating conjectures, (2) performing mathematical manipulations, (3) constructing evidence and providing justification for multiple solutions, (4) drawing conclusions from statements, and (5) verifying the validity of arguments. The findings show that indicator (1) reached the very good category with a percentage of 85.71%, while indicator (2) was categorized as good with 60.71%. Indicators (3) and (5) fell into the sufficient category with percentages of 32.14% and 46.43%, respectively. Indicator (4) was categorized as poor with 25.00%. Overall, the average percentage across all indicators was 50.00%, indicating that the mathematical reasoning ability of 11th-grade high school students in the school under study falls into the sufficient category. This study contributes to the existing body of knowledge by offering a detailed profile of students’ reasoning performance across multiple indicators, providing empirical evidence of specific reasoning weaknesses often overlooked in quantitative assessments, and highlighting the need for targeted instructional interventions to strengthen conceptual understanding and argumentation in mathematics learning.